Comparing the effect of sucrose gel and metronidazole gel in treatment of clinical symptoms of bacterial vaginosis: a randomized controlled trial - Khazaeian, Somayyeh (Trials, 2018)
BACKGROUND: Lactobacilli, as normal vaginal flora, have a central role in controlling body environment and preventing the growth of pathogens. Sucrose, by promoting the growth of Lactobacilli, accelerates the suppression of pathogenic bacteria. The aim of this research was to compare the effects of sucrose gel with those of metronidazole gel in treating women with bacterial vaginosis (BV). METHODS: This triple-blind clinical trial (IRCT2016112631105N1) was conducted with 70 sexually active, premenopausal women diagnosed with bacterial vaginosis through meeting at least three out of four Amsel criteria. The subjects were randomly divided into two groups of 35 patients, one group treated with sucrose vaginal gel, and the other with metronidazole vaginal gel. The treatment period was 14 days for each group. At the end of the treatment period, the status of each woman’s improvement was determined by elimination at least three out of four Amsel criteria (homogeneous vaginal discharge, presence of clue cells > 20%, positive whiff test and vaginal pH value > 4.5), and clinical complaints and reported side effects of medication were recorded for the patients. Data were analyzed using the t test, chi-squared test and McNemar’s test). RESULTS: The sucrose vaginal gel and metronidazole vaginal gel were not significantly different in reducing patients’ clinical complaints or in elimination at least three out of four of the Amsel criteria that were positive before treatment. With an 85.7% improvement rate with sucrose gel and an 88.5% improvement rate with metronidazole gel, the differences in therapeutic response were not significant, and neither was statistically different in improving the disease (p = 0.389). CONCLUSION: It seems that sucrose vaginal gel might be considered a possible alternative to metronidazole vaginal gel in the treatment of bacterial vaginosis. TRIAL REGISTRATION: Iranian Registry of Clinical Trials, IRCT2016112631105N1. Registered on 27 December 2016.